Visualizing and Animating Data in Python - O'Leary, Mike (My University, 2021)
There is a need for mathematicians and scientists, especially computer scientists, to be able to visualize and animate data. This hackathon will teach you how to set up your own Python development environment and use it to develop your own visualizations and animations.
Keywords: Mathematics; Python; Data visualization